Sintonização de ressonâncias plasmônicas de nanoestruturas de prata para detecção espectroscópica de glifosato em água - Costa, Lays de Carvalho Seixas (2019)
This work presents the development of a methodology able to detect the herbicide glyphosate in water using UV-Vis and Raman optical spectroscopy techniques.Rhodamine dye was used as probe molecule for preliminary testes, with the objective of developing a laser ablation and photo-induced shape conversion methodology capable of synthesizing nanoparticles with different geometries and dimensions. These nanoparticles presented different plasmon resonances and, when tuned to the laser pumping wavelength used in the Raman interrogations, show an optimization in the intensification of the electromagnetic field. Subsequently the dye was replaced by the herbicide glyphosate and the results show that with the use of spherical nanostructures it is possible to identify only one band in the 1806 cm-1 region of the surface enhanced Raman spectrum, with a signal-to-noise ratio of 5.70 for the lowest concentration used in the tests of 0.11 mg / L of glyphosate in solution. For the triangular and hexagonal silver nanostructures resulting from the photoconversion process, the spectrum was distinct with three new bands at 725, 935 and 1375 cm -1, herbicide’s figerprint regions, and a higher signal-to-noise ratio of 10.02 for the same glyphosate concentration. Such results were attributed to the tuning of the plasmon resonances and to the concentration of electromagnetic fields at the sharp edges of such structures.